2004
DOI: 10.1016/j.clpt.2003.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring amiodarone's toxicities: recommendations, evidence, and clinical practice

Abstract: Current standards for amiodarone toxicity monitoring are based on expert opinion with limited evidence to support most recommendations. Monitoring practices appear to vary significantly, with few patients receiving all of the recommended monitoring. Some amiodarone-related adverse drug events may be preventable and patient safety might be improved with a better understanding of monitoring processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
53
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 87 publications
(235 reference statements)
3
53
2
Order By: Relevance
“…7,17,19 These small studies all determined that thyroid function and liver enzymes were monitored in low percentages (23%-42%) of patients. 7,17,19 The current study was therefore undertaken to determine the rates of monitoring thyroid function and liver aminotransferases among ambulatory patients dispensed amiodarone therapy across 10 sites. Secondary objectives included determining the accuracy of administrative claims data for aminotransferase and thyroid function monitoring and describing patient factors associated with monitoring.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…7,17,19 These small studies all determined that thyroid function and liver enzymes were monitored in low percentages (23%-42%) of patients. 7,17,19 The current study was therefore undertaken to determine the rates of monitoring thyroid function and liver aminotransferases among ambulatory patients dispensed amiodarone therapy across 10 sites. Secondary objectives included determining the accuracy of administrative claims data for aminotransferase and thyroid function monitoring and describing patient factors associated with monitoring.…”
mentioning
confidence: 99%
“…The few studies that evaluated liver and thyroid monitoring among patients prescribed amiodarone were conducted at single clinics and/or included fewer than 100 patients. 7,17,19 These small studies all determined that thyroid function and liver enzymes were monitored in low percentages (23%-42%) of patients. 7,17,19 The current study was therefore undertaken to determine the rates of monitoring thyroid function and liver aminotransferases among ambulatory patients dispensed amiodarone therapy across 10 sites.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Despite published consensus statements recommending these monitoring requirements, patients receiving amiodarone may not always be appropriately followed. A recent review suggested about 50% of the patients starting amiodarone received minimum baseline evaluation and less than 25% received the recommended ongoing surveillance [8]. Several studies have also been published describing the need for amiodarone drug monitoring [9,10]; however, no universally accepted and feasible approach is available.…”
mentioning
confidence: 99%